Progress of tumor-associated macrophages in the epithelial-mesenchymal transition of tumor - Li, Xiaoxiao; Chen, Ling; Peng, Xiaobo; Zhan, Xianbao (Frontiers in Oncology, 2022)
As a significant public health problem with high morbidity and mortality worldwide, tumor is one of the major diseases endangering human life. Moreover, metastasis is the most important contributor to the death of tumor patients. Epithelial-mesenchymal transition (EMT) is an essential biological process in developing primary tumors to metastasis. It underlies tumor progression and metastasis by inducing a series of alterations in tumor cells that confer the ability to move and migrate. Tumor-associated macrophages (TAMs) are one of the primary infiltrating immune cells in the tumor microenvironment, and they play an indispensable role in the EMT process of tumor cells by interacting with tumor cells. With the increasing clarity of the relationship between TAMs and EMT and tumor metastasis, targeting TAMs and EMT processes is emerging as a promising target for developing new cancer therapies. Therefore, this paper reviews the recent research progress of tumor-associated macrophages in tumor epithelial-mesenchymal transition and briefly discusses the current anti-tumor therapies targeting TAMs and EMT processes.